Reducing the risk of athlete burnout: Psychosocial, sociocultural, and individual considerations for coaches. Issue 4 (August 2019) - Davis, Louise; Stenling, Andreas; Gustafsson, Henrik; Appleby, Ralph; Davis, Paul
Past research suggests that athletes' relationships with their coach can act as a risk factor in the development of burnout. Coaching practice may be enhanced through understanding the multidimensional factors that can augment the associations between coach–athlete relationship quality and athlete burnout. The present study explored both individual difference characteristics (gender, age, and sport level) and sociocultural factors (sport type) as moderators of this relationship. Our findings show statistically significant interaction effects for gender and age. Coaches and practitioners working with younger athletes and male performers in particular, are advised to work with strategies aiming to build relationships and reduce the risk of burnout.